PENERAPAN TEKNIK KEGEL EXERCISE UNTUK MENINGKATKAN ELIMINASI URIN PADA PASIEN BATU URETER DI RSUP DR TAJUDDIN CHALID - Iis Rizkiana; Yusrah Taqiah; Wan Sulastri Emin; Muhajirin Maliga (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Ureteral stones are one of the most common urological problems that often cause urinary elimination disorders such as retention, severe pain, and risk of complications. Management is generally focused on pharmacological therapy and invasive procedures, while non- pharmacological interventions are still rarely applied. Kegel exercise is a pelvic floor muscle training aimed at improving urinary control and enhancing urinary elimination. To determine the effectiveness of Kegel exercise in improving urinary elimination in the Emergency Department of Dr. Tajuddin Chalid General Hospital, Makassar. This study used a case study design involving a 21-year-old male patient diagnosed with ureteral stones. Nursing care was provided through assessment, diagnosis, intervention, implementation, and evaluation. The main intervention consisted of education and Kegel exercise training.Findings showed improvements in urinary elimination, including smoother urine flow, reduced complaints of incomplete voiding, and decreased pain intensity. Kegel exercise can serve as a simple, safe, and effective non pharmacological intervention to improve urinary elimination. Recommendation: This exercise may be considered as a supportive therapy in emergency nursing care for patients with urinary elimination disorders.